Heroes. Season 1 [videorecording (DVD)] - Kring, Tim, 1957- (Universal Studios Home Entertainment, 2012)
Niki harbors a secret dark side, cheerleader Claire heals from an injury, Japanese Dilbert Hiro can bend time and space, Senatorial candidate Nathan is able to fly, his brother Peter can copy others' powers, Matt is a cop who can read minds, and junkie artist Isaac sees the future. While Claire and Hiro explore the potential of their new powers, Niki and her son try to elude some hired thugs and end up overwhelmed by her dark side. Suresh searches for the answer to his father's death. Hiro takes a trip, five weeks into the future, to New York and sees the city destroyed by a massive blast. Isaac sees the same, but through his paintings. The Heroes begin slowly coming into contact through a haze of dreams, visions, murder, swords and death. They need to stop a serial killer and save New York.